Exploring the Language Usage in Mark Twain’s Novel “Adventures of Tom Sawyer”: Hegemonic Masculinity Analysis - Girsang, Martina; Sembiring, Elita Modesta; Silalahi, Veracy; Sianturi, Srisofian; Linda, Linda (REiLA : Journal of Research and Innovation in Language, 2022)
The practice of legitimizing men’s dominance is known as hegemonic masculinity, and it is a concept that has often been explored through numerous adult novels, but rarely in children’s literature. To address this research gap, this study conducted a text analysis on the types of hegemonic masculinity depictions in Mark Twain’s “Adventures of Tom Sawyer”, as one of the most read novels by young readers who attend schools with an international curriculum. The researchers used the descriptive qualitative method hand in hand with Connell and Messerschmidt’s theory of hegemonic masculinity. The result showed 3 types of hegemonic masculinity displayed in the novel include toxic masculinity, bad boy archetype, and dominant-submissive roles. These types can influence young to imitate bad role model, engage in bullying, and develop an unhealthy habit of hiding their feelings. Young readers may begin to see mischievous, manipulating, and aggressive behaviour as a common thing to do or even should be done to establish their place in society. Tom Sawyer is mandatory reading in the curriculum and is a classic that is unlikely to be taken off of the syllabus, so this study recommends teachers to make students become aware of the underlying ideas and values implicated in the novels. This study presented the implication for schools which assigned the reading of “Tom Sawyer” to address the reality of hegemonic masculinity in the novel to reduce the possible effect of its themes.